Menstruation, Hygiene Practice and Menstrual Distress in Female Undergraduate Students - Kumiko Kido; Ayana Hirai; Yuka Kasai; Yuko Uemura (Women, Midwives and Midwifery, 2022)
Background: Currently, there is no up-to-date survey on actual menstruation, including recent changes in the amount of menstrual blood loss in women as the age of the first menstruation decreases in Japan. Also, few study has examined whether temperature in clothing reflecting with basal body temperature and other factors are related to menstruation-associated symptoms. Purpose: The study aimed to determine the actual menstruation, the change in the number of sanitary napkins and menstrual distress during one menstrual cycle, and the predictive factors of menstrual distress. Methods: The samples were eight university students over the age of 20. This study was conducted from the end of June to the end of September 2020. They were asked to undertake the following: menstrual cycle, length of menstruation; the amount of menstrual blood loss; changing sanitary napkins; the Japanese version of the Menstrual Distress Questionnaire (J-MDQ). The J-MDQ consists of 47 questions answered on a scale of 0 to 3, with a higher score indicating more severe menstruation-related symptoms, within a week before, during and a week after menstruation. Multiple liner regression and Friedman test were conducted as statistical analysis. Results: The volume of menstrual blood loss increased drastically on the second day of the menstruation, and rapidly decreased from the third day. Napkin changing was also most frequent on the second day, however there is no correlation between the volume of menstrual blood and the number of times changing sanitary napkins after the second day of menstruation. The total J-MDQ during menstruation was significantly higher than pre and after menstruation (P<0.05). The duration of blood flow were associated with J-MDQ. Conclusions: Appropriate changing sanitary napkins needs to be recommended to improve for vulvar hygiene. The menstrual distress was highest during menstruation.